Pengaruh Rasio Likuiditas, Profitabilitas, Leverage dan Perputaran Piutang terhadap Financial Distress: (Studi Kasus Perusahaan Perbankan yang Terdaftar di BEI Periode 2021-2024) - Emilia Kurniawati; Nur Ainiyah; Nurdiana Fitri Isnaini (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to examine the effect of liquidity, profitability, leverage, and accounts receivable turnover on financial distress. The sample used in this study is banking companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. The population sample in this study is 47 companies. The sample was determined using a purposive sampling method, resulting in 10 companies. The type of data for this study is secondary data obtained from www.idx.co.id. The analytical method used was multiple regression analysis. The results of this study indicate that simultaneously, the variables liquidity, profitability, leverage, and accounts receivable turnover significantly influence financial distress. Partially, the liquidity variable has a negative and significant effect on financial distress, while the profitability variable has a negative and significant effect on financial distress. Leverage and accounts receivable turnover have no effect on financial distress. Furthermore, the Adjusted R-square coefficient is 95.3%, indicating that 4.7% is influenced by other variables. These findings suggest that companies with better liquidity and profitability levels have a lower probability of experiencing financial distress. This aligns with the theory that high liquidity ensures the availability of cash to meet short-term obligations, while strong profitability supports operational sustainability and investor confidence. On the other hand, leverage and accounts receivable turnover did not significantly affect financial distress, which may indicate that banking companies have a more stable debt structure and effective credit management, reducing their influence on distress conditions. This research provides practical insights for company management, investors, and regulators. For managers, maintaining optimal liquidity and profitability levels is essential to prevent financial difficulties. For investors, liquidity and profitability indicators can serve as reliable references for investment decision-making.